Older patients with traumatic brain injury present with a higher GCS score than younger patients for a given severity of injury. Issue 6 (29th January 2016) - Kehoe, A; Smith, J E; Bouamra, O; Edwards, A; Yates, D; Lecky, F
Abstract : Introduction: Recent evidence suggests that presenting GCS may be higher in older rather than younger patients for an equivalent anatomical severity of traumatic brain injury (TBI). The aim of this study was to confirm these observations using a national trauma database and to test explanatory hypotheses. Methods: The Trauma Audit Research Network database was interrogated to identify all adult cases of severe isolated TBI from 1988 to 2013. Cases were categorised by age into those under 65 years and those 65 years and older. Median presenting GCS was compared between the groups at abbreviated injury score (AIS) level (3, 4 and 5). Comparisons were repeated for subgroups defined by mechanism of injury and type of isolated intracranial injury. Results: 25 082 patients with isolated TBI met the inclusion criteria, 10 936 in the older group and 14 146 in the younger group. Median or distribution of presenting GCS differed between groups at each AIS level. AIS 3: 14 (11–15) vs 15 (13–15), AIS 4: 14 (9–15) vs 14 (13–15), AIS 5: 9 (4–14) vs 14 (5–15) all p<0.001. Similar differences between the groups were observed across all mechanisms of injury and types of isolated intracranial injury. We detected no influence of gender on results. Conclusions: For an equivalent severity of intracranial injury, presenting GCS is higher in older patients than in the young. This observation is unlikely to be explained by differences in mechanism of injury or types of intracranial injury between the two groups.